Physical Health Status in Multiple Sclerosis Patients in Tehran City - Jadidi Milani, maryam; Ashktorab, tahereh; Abedsaeedi, zhila; Alavi Majd, hamid (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim Symptoms of Multiple Sclerosis (MS) are unpredictable; they vary from person to person, and from time to time in the same individual . Research conducted in Iran, didn't focus specifically on the health status of MS. Therefore, we undertook this study on physical health status in MS patients . Materials and Methods This is a descriptive cross-sectional study on 119 MS patients, recruited through convenience sampling. Data were collected using the physical section of the "Multiple Sclerosis Quality of Life Inventory (MSQLI)", with 78 items and 0.93 Cronbach's coefficient that translated to Persian and adapted to Iranian culture by researchers. Findings The physical health status was moderate in 49.6%. The lowest mean score percent was for physical component 41.06 (12.9) and the highest mean score percent was for Impact of visual impairment 87.05(16.1). Physical components indicated a significant positive correlation with fatigue impact, pain effect and bladder control. We found a significant positive correlation between fatigue impact with pain effects, sexual satisfaction, and bladder and bowel control. Moreover, significant positive correlations were found between pain effects with sexual satisfaction and bowel control; sexual satisfaction and bladder and bowel control; bladder control and bowel control. Conclusion These findings may assist health care providers to identify patients at risk of aggravating physical health status; thus allowing appropriate and timely interventions to be conducted. Keywords : Multiple sclerosis, Physical health, Fatigue, Pain, Bladder Control, Bowel Control, Sexual Dysfunction, Visual Dysfunction. * Corresponding author: Tahereh Ashktorab, Assistant Professor, School of Nursing & Midwifery, Shahid Beheshti University of Medical Sciences E-mail: tashktorab@yahoo.com REFERENCES -Alimohamadi N Sadat S Abazari P (2006). [The experiences of patients with multiple sclerosis]. Iranian Journal of Nursing & Midwifery Research. 11(2). [Online].<http://nm.mui.ac.ir/journal/main.php?filename=article.php&nomagazine=31&noart=1&fo oter=footer1.php>. (Persian). -Benito-Leon J et al (2003). A review about the impact of multiple sclerosis on health-related quality of life. Disability and Rehabilitation. 25(12) 1291–1303. -Casetta I et al (2009) Gender differences in health-related quality of life in multiple sclerosis. Multiple Sclerosis. 15 (11) 1339–1346. -Dennison L Moss-Morris R and Chalder T (2009). A review of psychological correlates of adjustment in patients with multiple sclerosis. Clinical Psychology Review. 29 (2) 141-153. -Douglas C Wollin J Windsor C (2008). Illness and demographic correlates of chronic Pain among a community-based sample of people with multiple sclerosis. Archives of Physical Medicine and Rehabilitation. 89 (10) 1923-1932. -Fischer J et al (1999) Recent developments in the assessment of quality of life in multiple sclerosis (MS). Multiple Sclerosis. 5 (4) 51-259. -Füvesi J et al (2010). Factors influencing the health-related quality of life in Hungarian multiple sclerosis patients. Journal of the Neurological Sciences. 293 (1-2) 59–64. -Flensner G et al (2008). Fatigue in relation to perceived health: people with multiple sclerosis compared with people in the general population. Scandinavian Journal of Caring Science. 22 (3) 91-400. -Forbes A et al (2006). Health problems and health-related quality of life in people with multiple sclerosis. Clinical Rehabilitation. 20 (1) 67-78. -Fruehwald S et al (2001). Depression and quality of life in multiple sclerosis. Acta Neurologica Scandinanvia. 104 (5) 257-61. -Ghaem H Borhani Haghighi A (2008). The impact of disability, fatigue and sleep quality on the quality of life in multiple sclerosis. The Annals of Indian Academy of Neurology. 11(4) 36–241. -Higginson IJ et al (2006). Symptom prevalence and severity in people severely affected by multiple sclerosis. Journal of Palliative Care. 22 (3) 58-65. -“Just the Facts” National Multiple Sclerosis Society, 21 Dec 2008 [Online]. <http://www.nationalmssociety.org/aboutmultiple- sclerosis/what-is-ms/index.aspx>. [20 March 2009]. -Masoodi R et al (2008). [The effect of Orem based self-care program on physical quality of life in multiple sclerosis patients]. Journal of Shahrekord University of Medical Sciences. 10 (2) 21-30. (Persian). -Multiple Sclerosis Association of Iran (2010). [Activities Report of Multiple Sclerosis Association of Iran in 2009]. (Persian). -Patti F et al (2003). Health related quality of life and depression in an Italian Sample of Multiple sclerosis patients. Journal of the Neurological Sciences. 211 (1–2) 55–62. -Paul GM et al “Multiple Sclerosis Quality of Life Inventory: A User's Manual”. New York: National Multiple Sclerosis Society, 1997 [Online].<http://walkcoc.nationalmssociety.org/docs/HOM/MSQLI-Manual-and-Forms.pdf>.[10 April 2009]. -“Process of translation and adaptation of instruments”. World Health Organization, 2009. [On line]. [cited 2 August 2009].< http://www.who.int>.>.[10 September 2009]. -Shahbeigi S (2010). 7 th International Congress of Multiple Sclerosis Tehran, Iran. Medical News. 1. (Persian). -Smeltzer S Bare B Hinkle J and Cheever K (2008). Brunner and Suddarth’s Textbook of Medical Surgical Nursing. 11 th edition. Volume 2. Philadelphia, Lippincott. -Tepavcevi 1 D Pekmezovi1 T Drulovi1 J (2009). Quality of life assessment in patients with multiple sclerosis. Vojnosanit Pregl. 66 (8) 645-50. -Turpin K et al (2007). Deterioration in the health-related quality of life of persons with multiple sclerosis: the possible warning signs. Multiple Sclerosis. 13 (8) 1038–1045. -Vanner EA et al (2008). Pilot Study Exploring Quality of Life and Barriers to Leisure-time Physical Activity in Persons with Moderate to Severe Multiple Sclerosis. Disability and Health Journal. 1 (1) 58-65. -Vazirinejad R Lilley J Ward C (2008). A health profile of adults with multiple sclerosis living in the community. Multiple Sclerosis. 14 (8) 099–1105. -Visschedijk M et al (2004). Value of Health-related Quality of Life to Predict Disability Course in Multiple Sclerosis. Neurology. 63 (11) 2046-50. -“What is Multiple Sclerosis?” Multiple Sclerosis Association of America, 2008. [On line].<http://www.msassociation.org/about_multiple_sclerosis/whatisms>. [22 March 2009